A Case of Serratia marcescens Endocarditis in a Nonintravenous Drug-Using Male Patient and Review of Literature. (20th June 2019) - Nikolakopoulos, Achilleas; Koutsogiannis, Nikolaos; Xaplanteri, Panagiota; Gogos, Charalambos; Kolonitsiou, Fevronia; Lekkou, Alexandra
Abstract : Introduction . Serratia marcescens is a rare cause of infective endocarditis and has almost exclusively been associated with intravenous drug use and hospital-acquired infections. Here, we present a case of infective endocarditis caused by Serratia marcescens in an otherwise healthy, nonintravenous drug-using male patient. Case Report . A 41-year-old man presented with hypertension and hemoptysis. Blood cultures were obtained that showed bacteremia by Serratia marcescens . An echocardiogram was carried out that revealed severe mitral regurgitation accompanying ruptured mitral chordae tendineae. The patient received the appropriate antibiotic treatment, without further surgical intervention. Discussion. Hospital-acquired infections by Serratia species are a common problem in medical practice and have been attributed to specialized interventional procedures. Taking into consideration the patient's immunocompetence and lack of intravenous drug use, it is possible that bacteremia could be attributed to a medical procedure. Moreover, in contrast to most cases described in the literature, no surgery was performed.